Effects of AIMР1/p43 and EMAP II Proteins on Malignant Tumor Cells - Kolomiiets, Mariia; Zayets, Volodymyr; Zaika, Leonid; Bolsunova, Olga; Kornelyuk, Oleksandr (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):306